Field‐Effect Transistors Using Thin Flakes of Misfit Layer Compound (LaS)1.20CrS2. Issue 20 (14th August 2017) - Shimazu, Yoshihiro; Takanashi, Masaya; Kurihara, Daiki; Fujisawa, Yutaro; Arai, Kensuke; Iwabuchi, Tatsuya; Suzuki, Kazuya
Abstract: Misfit layer compounds consist of two sublattices that are incommensurately modulated. These sublattices have the structures of cubic monochalcogenide and transition‐metal dichalcogenide monolayers. In this work, a semiconducting misfit layer compound (LaS)1 . 20 CrS2 is synthesized by chemical vapor transport. In absence of intervening LaS layers, a CrS2 layer does not exist in a stable state. Using thin flakes of (LaS)1 . 20 CrS2 obtained by mechanical exfoliation, field‐effect transistors are fabricated. The devices show n‐type transport characteristics. An on/off ratio of ≈250 (at 120 K) and mobility of 0.3 cm 2 V −1 s −1 (at room temperature) are observed. Temperature dependence of the conductance obeys thermal activation with the activation energy nearly linearly dependent on the gate voltage. This gate‐voltage dependence suggests that the density of trap states is considerably larger than that of MoS2 thin flakes. Abstract : Field effect transistors are fabricated using a semiconducting misfit layer compound, (LaS)1 . 20 CrS2, as a channel material. The devices exhibit n‐type transfer characteristics and thermally activated transport with the activation energy linearly dependent on the gate voltage. Misfit layer compounds associated with unique structural properties offer new opportunities in the research of 2D materials.